PENINGKATAN PENGETAHUAN SISWA DALAM MEMILIH JAJANAN MAKANAN DI LEMBAGA PENDIDIKAN PERMATA JANNATI KOTA BANJARMASIN TAHUN 2016 - Achmad Rizal; Agus Jalpi (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
The quality of human resources improve is considered a key factor it takes to execute national development. Food hawker school is problems that need to be an attention for the community, especially the people old, educator, and the school management. Food and hawker school principal is at risk to biologist or chemically dirt. The results of supervision food hawker school children by BPOM of Indonesia in 2010 shows that of 2945 samples to be taken in 26 the capital provinces in Indonesia 48,35 % did not qualified. Snack habits at the school very useful if take-out is meeting requirements health, so that it could complete or add needs child nutrition these extension aims to tense knowledge students to hawker of healthy food, a participant in these extension were elementary school students in research institutes Permata Jannati Banjarmasin.